2008
DOI: 10.1007/s12185-008-0040-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA alleles with non-Hodgkin’s lymphoma in Korean population

Abstract: Several studies have been performed on the association between non-Hodgkin's lymphoma (NHL) and the presence of certain human leukocyte antigens (HLA) class II alleles in Asian countries, and these studies have shown different results, according to the ethnicity, for the frequencies of the HLA class II alleles, and especially for HLA-DRB1. Therefore, the distribution of the HLA-A, B, C, DRB1, and DQB1 alleles in 89 Korean patients with NHL and also in 200 healthy Korean controls was investigated in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Of additional interest was the identification of four genes in the major histocompatibility complex, class I (HLA-A, HLA-B, HLA-C, and HLA-E), which were all significantly upregulated following CRY2 silencing. Apart from being central to immune regulation, these genes have been associated with several cancers, including Hodgkin’s disease (49) and non-Hodgkin’s lymphoma (50). Taken together, these results suggest that reductions in CRY2 have the potential to significantly impact processes relevant for lymphomagenesis, and while they represent a first step in understanding the mechanism by which SNPs in the CRY2 gene might influence NHL susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Of additional interest was the identification of four genes in the major histocompatibility complex, class I (HLA-A, HLA-B, HLA-C, and HLA-E), which were all significantly upregulated following CRY2 silencing. Apart from being central to immune regulation, these genes have been associated with several cancers, including Hodgkin’s disease (49) and non-Hodgkin’s lymphoma (50). Taken together, these results suggest that reductions in CRY2 have the potential to significantly impact processes relevant for lymphomagenesis, and while they represent a first step in understanding the mechanism by which SNPs in the CRY2 gene might influence NHL susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Several small studies have reported links between MHC Class II alleles and NHL9,10,11, with somewhat conflicting results that may be attributable to small sample size, the combined analysis of mixed NHL subtypes, and/or differences in ethnic groups being analyzed11. In a large pooled study within the InterLymph consortium, the variant allele for TNF -308G>A (rs1800629) and a TNF/LTA haplotype located in the MHC Class III region were positively associated with DLBCL risk, but no association was found for FL12.…”
mentioning
confidence: 99%
“…The US FDA recommends screening for HLA-B*1502 allele in most of Asian ancestry before initiating carbamazepine therapy. In this background, recent result in Korean population showed that the frequencies of A*3101 in CBZ-induced HSS/SCARs were significantly higher than those in CBZ-tolerant controls (35). The frequencies of A*3101 in CBZ-induced HSS/SCARs and B*1511 in carbamazepine-induced SJS were significantly higher than those in the general population (36).…”
Section: Drug-induced Adverse Effects (Table V)mentioning
confidence: 89%
“…But, these studies have shown different results, according to the ethnicity. In Koreans, HLA-B51, DRB1*09, DQB1*03 and B51-DRB1*09-DQB1*03 haplotype were positively associated with NHL (35). …”
Section: Infectious Diseases and Cancers (Table Iv)mentioning
confidence: 99%